Locally Advanced Pseudopapillary Neoplasm of the Pancreas in a Male Patient: A Case Report - Attaallah, Wafi; Javadov, Mirhalig; Ayranci, Fatma Gulcicek; Filinte, Deniz; Dulundu, Ender; Yegen, Cumhur (JOP. Journal of the Pancreas, 2013)
Context Solid pseudopapillary tumor of the pancreas is a rare neoplasm, predominantly observed in young women and with greatest incidence in the second and third decade. Although large at the time of diagnosis, it has clinically good behavior. The occurrence of infiltrating varieties of solid pseudopapillary tumors is very rare. We report the case of a 48-year-old man with a giant mass in the pancreas, incidentally discovered during an abdominal ultrasonography. The mass was later investigated using multidetector computed tomography and magnetic resonance imaging. The lobulated lesion had cystic-necrotic appearances which lead the radiologists to suggest the possibility of either a gastrointestinal stromal tumor or a pancreatic cancer. The patient was operated. Operative signs showed that the tumor invaded the splenic hilum and mesentery of transverse colon. En-block resection of pancreas, spleen and transverse colon was performed as the mass was thought to be a locally advanced pancreas tumor. Pathological diagnosis reported a solid pseudopapillary tumor. Conclusion Although solid pseudopapillary tumor is considered a rare tumor, with a very rare rate of locally infiltrating variety, and rarely presents in males, it must be kept in mind while making the differential diagnosis of cystic pancreatic lesions to begin appropriate clinical management. Image: Microscopic findings of solid-pseudopapillary neoplasm.